The effect of job satisfaction, intrinsic motivation, and extrinsic motivation on the turnover intention of contract workers dr Fauziah Bireuen Hospital - Hanum, Wulan Farida; Khairawati, Khairawati; Marbawi, Marbawi; Azhar, Azhar (Management Research and Behavior Journal, 2023)
This study aims to determine the effect of job satisfaction, intrinsic motivation, and extrinsic motivation on the turnover intention of contract workers at dr Fauziah Bireuen Hospital. This study used primary data by distributing questionnaires to 100 contract workers using the Census sample method. Methods of data analysis in this study using multiple linear regression analysis. The results partially show that job satisfaction negatively and significantly affects turnover intention, intrinsic motivation negatively and significantly affects turnover intention, and extrinsic motivation negatively and significantly affects turnover intention. Simultaneously, job satisfaction, intrinsic motivation, and extrinsic motivation positively and significantly affect the turnover intention of contract workers at dr Fauziah Bireuen Hospital.